Implementation of Learning the Kitab of Sulam Tashil to Master the Qawaidunnahwi of Students of the Al-Mubaarok Islamic Boarding School, Manggisan, Wonosobo - Zaqiyah, Khoeru; Sunarko, Asep; Linnaja, Ngatoillah (AJIRSS: Asian Journal of Innovative Research in Social Science, 2024)
The purpose of the study is to: 1) Describe the implementation of learning the kitab of Sulam Tashil in helping students of the Al-Mubaarok Manggisan Wonosobo Islamic Boarding School in understanding the rules of nahwu science; 2) Identify factors that support and hinder the process of learning the kitab of Sulam Tashil in mastering qawāʿid al-naḥwī by students; 3) Find out the extent to which the results of the implementation of learning the kitab of Sulam Tashil in improving students' understanding of nahwu science. This study uses a qualitative approach with a type of field research. Data collection techniques used include direct observation, interviews with related informants, and documentation of various written and visual data. The data analysis techniques applied consist of three stages, namely reducing data, presenting data, and drawing final conclusions based on findings in the field. The study's results indicate that: 1) The implementation of learning the Kitab of Sulam Tashil in mastering qawaidunnahwi has run smoothly, from planning to implementation, following the procedures in the Kitab of Sulam Tashil. The advantages of understanding the kitab of Sulam Tashil lie in using other kitabs to increase students' mastery of qawaidunnahwi. 2) Supporting factors for learning include the quality of competent teachers, the use of simple Javanese in delivering material, and interactive teaching methods such as sorogan and group discussions. Inhibiting factors for learning include the difficulty of some students in translating material from Javanese to Indonesian. 3) The learning results show that most students can master the rules of nahwu gradually and are carried out in the form of oral tests, written tests, presentations, and memorization as indicators of fairly good mastery of the material.